Validation of the american quality assessment model and performance improvement to the brazilian transplant - Letícia de Fatima Lazarini; Linda Ohler; Janine Schirmer; Bartira de Aguiar Roza (Universidade de São Paulo, 2020)
Objective: To validate the quality assessment and performance improvement instrument of US transplant programs to the Brazilian reality. Method: Methodological study developed for semantic validation and cultural adaptation of the Quality assessment and Performance Improvement instrument in the following steps: 1) translation; 2) synthesis; 3) back translation; 4) review by expert committee; 5) pretest and 6) content validation. To evaluate the agreement between the five judges, the Kappa coefficient was used and for content validation, the content validation index. Results: Kappa coefficient showed the agreement of the judges for semantic, idiomatic, cultural and conceptual equivalences. Content validation index values for relevance and item sequence of at least 0.80 for all blocks. Conclusion: The instrument of Quality Evaluation and Performance Improvement of Transplantation Programs proved to be valid and reliable. This instrument will contribute to the development of quality assurance programs for transplant teams in Brazil.